HOW LEADERSHIP STYLES, AUTONOMY AND CONSCIOUSNESS LEVELS AFFECT TEAMWORKING EFFECTIVENESS ON THE SHOP FLOOR? - Bastos, Fábio Augusto Darella de Assis; Barretiri, Leandro Augusto; de Mello Cordeiro, José Vicente Bandeira (Caderno PAIC, 2017)
The purpose of this paper is to describe how leadership profile, teams’ level of autonomy and team members’ consciousness level interact to affect teams’ effectiveness in terms of knowledge management. To achieve this overall objective, this paper established, based on literature, a theoretical-conceptual model (construct) that relates the variables, namely, leadership profile in teams, autonomy of work within teams, team members’ consciousness levels and teams’ effectiveness, in order to validate the proposed model with specialists on the related areas. The research method adopted was the Delphi method, which proposes the deduction and refinement of opinions of a group of experts, whose intention is to find the common sense of the opinions of these specialists through questionnaires and feedback. Specialists concluded that, the higher the complexity of team members’ consciousness level and their values, the more effective are the more autonomous teams’ design and the more democratic leadership approaches. This proposed model was validated by the specialists, enabling the implementation of a quantitative survey on companies with different profiles, in order to aplly the defined model on actual shop floor teams to test its effectiveness on predicting how effective a team can be depending on their members’ level of consciousness and values and the leadership approaches.